Improving Learning Outcomes Of Front Roll On Floor Gymnastics Through A Game Model In Class IV Students Of Primary School Negeri 70 Lubuklinggau - Triwijaya, Restu (CV Media Inti Teknologi, 2024)
This study aims to determine the role of the game model in improving the learning outcomes of fourth grade students of SD Negeri 70 Lubuklinggau by analyzing data on learning outcomes obtained from learning in cycle I and cycle II. This research is a classroom action research conducted collaboratively and participatively with peers. The research subjects were fourth grade students of SD Negeri 70 Lubuklinggau in the odd semester of the 2023/2024 academic year, totaling 27 students. The results showed that the teaching and learning process of forward rolling improved from cycle I and cycle II, as evidenced from cycle I the average student activity reached 48.75% with sufficient criteria, cycle II reached 72.5% with good criteria. Cycle I teacher skills reached 57.5% with sufficient criteria, cycle II 73.75% with good criteria. Based on data analysis, it can be concluded that learning front roll floor exercises through a game model can improve student learning outcomes. Initial data obtained from cycle I class average of 66.66% or a total of 18 students who meet the KKM standard of 70, while 9 students or 33.33% have not met the KKM. The average score at the end of cycle II increased to 24 or 88.88% who met the KKM and 3 students or 11.11% below the KKM.